Motor-driven gene expression - Jarvis, Erich D. (The National Academy of Sciences of the USA, 1997)
There is increased neuronal firing in the high vocal center (a motor nucleus) and other song nuclei of canaries, Serinus canaria, and zebra finches, Taeniopygia guttata, whenever these songbirds sing or hear song. These observations suggested that song perception involved sensory and motor pathways. We now show that the act of singing, but not hearing song, induces a rapid and striking increase (up to 60-fold) in expression of the transcriptional regulator ZENK in the high vocal center and other song nuclei. This motor-driven gene expression is independent of auditory feedback, since it occurs in deafened birds when they sing and in muted birds when they produce silent song. Conversely, hearing song, but not the act of singing, induces ZENK expression in parts of the auditory forebrain. Our observations show that even though the same auditory stimulus activates sensory and motor pathways, perception and production of song are accompanied by anatomically distinct patterns of gene expression.